A cut above? Inferior vena cava resection without reconstruction: a dual-centre experience. (July 2021) - Noël, Jonathan P; Tang, Sarah Yu Weng; Muhammad, Nana Aishatu Liman; Nicol, David; Kockelbergh, Roger C
Objectives: To evaluate outcomes in our patients undergoing inferior vena cava (IVC) resection without reconstruction, as part of an adrenal/renal cell cancer (RCC) operation. Methods: British Association of Urological Surgeons (BAUS) Data and Audit System records were obtained for two operating surgeons, each at geographically separate urological cancer centres. Retrospectively reviewed case notes of patients who had undergone IVC resection without reconstruction as part of an adrenal/RCC operation, assessing operative parameters, length of stay, complications and follow-up status. Results: A total of Twenty-eight patients (20 right-sided tumours, 8 left sided) underwent IVC resection without reconstruction in May 2013–February 2017. No perioperative or early deaths occurred. Fourteen patients (50%) had complications: sepsis; pneumonia; congestive cardiac failure; acute kidney injury; symptomatic peripheral deep venous thrombosis; splenectomy; and significant chyle leak. At a median follow-up of 21 months (range 1–55 months) six patients (21.4%) have died and two patients (7.1%) progressed to metastatic disease, giving a 71.4% progression-free survival in this series. Conclusions: This case series illustrates our experience of IVC resection without reconstruction as an acceptably safe procedure. This should be considered as an alternative to graft reconstruction, particularly as minimal invasive approaches are being adopted. Level of Evidence: 3